Dual‐mode linearity enhanced power amplifier with wideband AM‐PM compensation for 5–6‐GHz FeLAA applications. Issue 5 (8th December 2021) - Li, Jiajin; Zhang, Zhihao; Zhang, Gary
Abstract: This letter presents a 5–6‐GHz dual‐mode power amplifier (PA) realized for further enhanced licensed assisted access application of downlink transmission. The output matching network with multiple harmonic traps and the wideband AM‐PM compensation technique are used in the design. To achieve high linear output power with less variation in the wide frequency range, different bias voltages of the first stage PA are set for dual‐mode operation. In the range 5–6 GHz, the PA delivers > 30 dBm saturated output power and reaches 24.4–24.8 dBm linear power at −35 dBc adjacent channel leakage ratio.